Conceptualizing and measuring party-interest group relationships. (November 2021) - Allern, Elin Haugsgjerd; Otjes, Simon; Poguntke, Thomas; Hansen, Vibeke Wøien; Saurugger, Sabine; Marshall, David
Relationships between political parties and interest groups form structures that enable and constrain political action. Yet there is a lack of consensus on what 'party-group relationships' means. We propose a conceptualization focusing on ties as means for structured interaction, which is different from sharing or transfer of resources and ideological kinship. Our conceptual discussion suggests that organizational ties form a single yet hierarchical scale of strength: groups that have many formal ties with particular parties would also have weaker (ie, less formal) ties with these parties, but not vice versa. To validate our conceptual map, we furthermore check whether the distinction between organizational ties, resource sharing/provision and ideological kinship holds empirically. We explore our expectations by means of novel interest group survey data from seven mature democracies. The results of our scaling analysis provide support for our predictions and have multiple implications for future research on the causes and effects of party-group relationships.